PEMODELAN DINAMIK KERETA MENGGUNAKAN BOGIE JENIS NT-60 DENGAN BANTUAN PROGRAM NASTRAN - Imam Santoso, Teguh
Abstract: Work performance of railways always be related to safety factor and riding comfort. Riding comfort is in connection with human sensitivity as a passenger toward vibration on horizontal and vertical direction caused by unalignment rail. Riding quality of railway is ability of bogie suspension system to reduce vibration occur so that it resulted a comfortable condition without causing train damage. Bogie NT-60 is a kind of common bogie that used for railway operational. Train dynamic modelling used component element method in longitudinal and lateral direction. Dynamic model consists of 7 elements, that is train body, front and rear bogie frame and 4 wheel-sets. Each of the element is connected by suspension system. The modelling and its analysis used Nastran programme so that it obtained response at train floor in the shape of time domain acceleration. Fast Fourier Transform (FFT) used Matlab programme was obtained frequency domain acceleration response that will show riding quality of train. Using Nippon Sharyo Ltd.- Japan Standard that refered to Janeway method, riding quality of train could be classified for velocities 30 and 70 kmslhour on different frequency interval. The analysis results from this modelling shown that most of all riding qualities were very good category, exception for velocity 30 kmslhour on frequency interval 200 Hz lateral direction and mixed frequency interval vertical direction were not tolerable category.